2020
DOI: 10.1002/bit.27481
|View full text |Cite
|
Sign up to set email alerts
|

Adipose stem cell‐derived extracellular matrix represents a promising biomaterial by inducing spontaneous formation of prevascular‐like structures by mvECs

Abstract: Tissue constructs of physiologically relevant scale require a vascular system to maintain cell viability. However, in vitro vascularization of engineered tissues is still a major challenge. Successful approaches are based on a feeder layer (FL) to support vascularization. Here, we investigated whether the supporting effect on the self‐assembled formation of prevascular‐like structures by microvascular endothelial cells (mvECs) originates from the FL itself or from its extracellular matrix (ECM). Therefore, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…It was found that acdECM from both time points [acdECM d7: 2357.6 (±201.1)% (this value was already published by us in Nellinger et al 2020) and acdECM d14: 2329.4 (±118.7)%] exhibited a higher degree of swelling compared with dECM [1288.1 (±383.3)%]. Further, acdECM exhibited a higher degree of swelling compared with scdECM d7 [scdECM d7: 1624.3 (±96.4)% (this value is already published by us in Nellinger et al 2020)] independent of the day. The degree of swelling of scdECMd14 [1764.5 (±421.0)%] was significantly lower compared with acdECM d7, within the different evaluation days of cdECM.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…It was found that acdECM from both time points [acdECM d7: 2357.6 (±201.1)% (this value was already published by us in Nellinger et al 2020) and acdECM d14: 2329.4 (±118.7)%] exhibited a higher degree of swelling compared with dECM [1288.1 (±383.3)%]. Further, acdECM exhibited a higher degree of swelling compared with scdECM d7 [scdECM d7: 1624.3 (±96.4)% (this value is already published by us in Nellinger et al 2020)] independent of the day. The degree of swelling of scdECMd14 [1764.5 (±421.0)%] was significantly lower compared with acdECM d7, within the different evaluation days of cdECM.…”
Section: Resultssupporting
confidence: 68%
“…Degree of swelling. The degree of swelling was calculated from the dry and wet weight of ECM samples according to Equation (3) and displayed in percentual amount (¥ = data from Nellinger et al, 2020; ** p ≤ 0.01; *** p ≤ 0.001; n = 9). ECM, extracellular matrix…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 2 × 10 5 of the control and DEHP-exposed (mock-treated and ENG knockdown) MDA-MB-231 cells were seeded in 6-well plates and incubated overnight. After incubation, serum-free culture medium was replaced, and cells were incubated for 48–72 h. Culture medium was collected and used to perform VEGF quantification using a Human VEFG 165 Standard TBM ELISA Development kit (900-T10, PEPROTech, Hamburg, Germany), as described previously [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Next to the interaction with ECM, bioactive molecules such as growth factors are known to be bound to ECM and might enhance proliferation. We previously demonstrated the presence of different growth factors in ASC‐derived ECM [29] . As there are no differences between the approaches with coECM and the functionalized ECMs (AzECM and CpECM), the functionalization exhibits no effect on the parameters shown in Figure 5 (cellular survival, proliferation, and metabolic activity) and therefore represents a promising method for ECM modification without unintentionally affecting cellular behavior.…”
Section: Resultsmentioning
confidence: 98%